BLOOD-SOAKED FEATHERS: URBAN FARMING MEETS URBAN FLOOD CONTROL-CREATED HABITATS - Nash, Susan Smith (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This piece explores the unintended clashes due to the recent surge in farming in urban neighborhoods and ecosystem modifications due to the need for aggressive flood control in rapidly growing urban areas.